2018
DOI: 10.1111/1753-6405.12802
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and body mass shape quality of life trajectories in mid‐age women

Abstract: Objective: To determine the combined longitudinal effect of body mass index (BMI) and physical activity (PA) on health‐related quality of life (HrQoL), using the SF‐6D (SF‐36) utility measure. Methods: Five waves of self‐reported data from the 1946–51 cohort (n=5,200; data collection, 2001–2013) of the Australian Longitudinal Study on Women’s Health were used. Mixed effect models were employed to address the objective. Results: Women with high PA experienced higher HrQoL regardless of BMI group, however, for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…However, there are other factors that have been shown to affect the QOL of the general population, but their influence on the QOL of university students has yet to be properly studied. These factors include diet [21], physical activity [22], smoking [23], alcohol intake [24] and relationship status [25]. Furthermore, most of the scholarly literature on the QOL of university students has focused on specific groups of students: generally those enrolled in health science programs (e.g., medicine, dentistry or nursing).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are other factors that have been shown to affect the QOL of the general population, but their influence on the QOL of university students has yet to be properly studied. These factors include diet [21], physical activity [22], smoking [23], alcohol intake [24] and relationship status [25]. Furthermore, most of the scholarly literature on the QOL of university students has focused on specific groups of students: generally those enrolled in health science programs (e.g., medicine, dentistry or nursing).…”
Section: Introductionmentioning
confidence: 99%
“…These current discoveries confirm physical activity as a quality of life determinant. A similar finding in later work, a prominent result in a five-year longitudinal study of women's health declared those no physical activity encounters an extreme decline in quality of life over time (Kanesarajah, Waller, Whitty, & Mishra, 2018). An empirical study claimed that constant physical activity is valuable to maintain health, whichever has a practical impact on psychology, well-being, cognitive developments, and levels of optimism (Heiestad, Rustaden, Bø, & Haakstad, 2016).…”
Section: Resultsmentioning
confidence: 57%
“…In turn, the positive influence of regular physical activity on the body composition and physical fitness of various population groups, including senior women, has been confirmed in research at various centres [8,12,13,26,28,30,39]. In these studies, a positive effect has also been demonstrated with regard to moderate and high physical activity in mitigating the effects of overweightness and obesity, which reduce quality of life among middle-aged women [18]. The positive effect of systematic physical activity on the content of adipose tissue and BMI in people aged 40-69 in Great Britain [7] and on physical fitness, health and BMI in people aged 33-76 in Germany [38] has been further confirmed.…”
Section: Discussionmentioning
confidence: 78%